Comparison of regional with general anesthesia on mortality and perioperative length of stay in older patients after hip fracture surgery. (17th November 2018) - Nishi, Takumi; Maeda, Toshiki; Imatoh, Takuya; Babazono, Akira
Abstract: Objective: The aim of this study was to examine whether anesthetic technique is associated with 30- or 90-day mortality and perioperative length of stay (LOS). Design: We used a retrospective cohort design using a healthcare insurance claims database. Setting: The Fukuoka Prefecture's claims database of older patients who underwent hip fracture surgery under general or regional (spinal or epidural) anesthesia from April 2012 to March 2016 was used for analyses. Participants: The database under analyses contained 16 125 participants of hip fracture surgery under general or regional anesthesia. Main Outcome Measure: We measured 30- and 90-day mortalities and perioperative LOS. Results: In a propensity score-matched cohort, we found no significant differences in 30- and 90-day mortalities after adjusting for confounding factors. The reconverted perioperative LOS for the general and regional anesthesia groups was, respectively, 29.7 (29.1–30.4) and 28.0 (27.4–28.6) days in the matched cohort. Therefore, the perioperative LOS in the regional anesthesia group was significantly shorter by 1.7 days than in the general anesthesia group ( P < 0.001). Conclusions: This study demonstrated that the use of regional anesthesia was not associated with 30- or 90-day mortality, but it was associated with slightly shorter perioperative LOS. Since Japan has much longer LOS than other countries, our findings have implications for more efficient healthcare resource utilization and quality assurance in geriatric care.